(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present paper provides model for mechanism of blood flow as Newtonian flow together with interpretation and limitation of the model. Here the term blood flow denotes that blood is carried from the heart to various parts of the body through a system of elastic tubes, e.g., the arteries, capillaries and vein and eventually returned to the heart without actually leaving the system. In order to form a mathematical model, we now formulate a simple mathematical model for blood flow in arteries by making assumption blood is a homogeneous fluid, its flow is steady or laminar and arteries are rigid, long straight. Here Newtonian flow is defined as that flow where shear stress is directly proportional to shear rate. Finally in interpretation of the model we get a formula is commonly used in laboratories for finding the viscosity of a given fluid and its velocity component.